Influência da argamassa de assentamento no comportamento de prismas estruturais de blocos vazados de concreto - Santos, Gabriela Spiller Bello dos (2017)
The structural masonry is a constructive system in which masonry exerts, also, the support function in the building and even though it is a relatively old technique, it is a field that still presents a great deficit of specialized research. To change this scenario, it is necessary to know the performance of the structural masonry, evaluating its mechanical performance and distinguishing the influence of each component involved (SILVA, 2004). Like this, the purpose of this work was to determine the influence of mortar laying on the behavior of structural prisms with cast concrete blocks, contributing to the technological development of this constructive system. For this, three types of laying mortar, produced with different a/c ratios and different binder contents (cement and lime), were evaluated in order to evaluate the influence of their deformation capacity and their mechanical resistance on the behavior of the prisms. It was possible, then, to conclude that mixed mortars (with lime), produce weaker and more deformable mixtures and, consequently, prisms with lower bearing capacity and greater deformation capacity. However, cement mortars, which are more resistant and less deformable, produce prisms with higher bearing capacity and less deformation capacity. Though, the increase in resistance of the prisms with increasing mortars resistance is not significant, but is approximately linear.